1982
DOI: 10.1042/bj2030361
|View full text |Cite
|
Sign up to set email alerts
|

Location and properties of two isoenzymes of cardiac adenylate kinase

Abstract: Adenylate kinase catalyses the equilibrium 2ADP = ATP + AMP. There are two isoenzymes of adenylate kinase in bovine ventricular tissue, one cytoplasmic, the other mitochondrial. Mitochondrial subfractionation locates this isoenzyme between the mitochondrial membranes with fatty acid-CoA ligase. The cytoplasmic and mitochondrial isoenzymes are distributed in ratio 3:2, and both forms were purified to homogeneity. They differ principally by charge, Km values for ATP, ADP and AMP, pH-stability and -activity prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…The extent of mitochondrial AK activity depends very much on the method of preparation, the tissue, and the species. It could be varied from as high as 40% in intact crude mitochondrial preparation obtained from hypo-osmatic bovine cardiac homogenates down to 0.3 % of the total activity in bovine aorta smooth muscle cells [19]. It is usually found to be around 10% and the rest accounted as cytosolic isoenzyme.…”
Section: Muscle Adenylate Kinasementioning
confidence: 98%
See 2 more Smart Citations
“…The extent of mitochondrial AK activity depends very much on the method of preparation, the tissue, and the species. It could be varied from as high as 40% in intact crude mitochondrial preparation obtained from hypo-osmatic bovine cardiac homogenates down to 0.3 % of the total activity in bovine aorta smooth muscle cells [19]. It is usually found to be around 10% and the rest accounted as cytosolic isoenzyme.…”
Section: Muscle Adenylate Kinasementioning
confidence: 98%
“…Part of the cytosolic AK is bound to myofibrils and is called myofibrillar AK [17][18][19]. The mitochondrial AK is located between the mitochondrial membranes with fatty acid-CoA ligase [14,19]. The extent of mitochondrial AK activity depends very much on the method of preparation, the tissue, and the species.…”
Section: Muscle Adenylate Kinasementioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the mitochondrial adenylate kinase (AK2 isoform) in heart muscle has the highest affinity (lowest K m ) for AMP (≤10 μM) amongst AMP metabolizing enzymes. 7,18 In addition, in the mitochondria-like kinetoplast organelle, the K m for AMP (AK2) is 74 μM.…”
Section: Discussionmentioning
confidence: 99%
“…An apparent Mr could be estimated as 23.5 kilodaltons. This Mr of monomer en zyme differed slightly from the other enzyme in bovine heart muscle (21,500), rabbit skel etal muscle (cytosolic, 21,000), and bovine heart mitochondria (31,500) [31,32], Fur ther genetic studies may be necessary for the structural analyses. As before, in the case of the rabbit-and calf-muscle enzymes [30], the steady-state kinetics of the aortic smooth muscle AK, at pH 7.4 (25 °C) and essentially fixed (172) at 0.16-0.18 seem to be adequately expressed by a random quasi-equilibrium type of mechanism with a rate-limiting step largely at the interconversion of the ternary com plexes.…”
Section: Partial Purification Of Ak Isoform From Bovine Aorta Smooth mentioning
confidence: 99%